STATUS GIZI DAN PENYELENGGARAAN MAKANAN DIET PASIEN RAWAT INAP DI BLU PROF. DR. R.D. KANDOU MANADO - Olga Lieke Paruntu (Jurnal GIZIDO, 2013)
Background: Nutritional Care in hospital nutrition services that are tailored to the patientand the clinical situation, nutritional status, and metabolic status of the body. Nutritional stateof the patient is very influential in the healing process, and vice versa course of the diseaseprocess can affect the nutritional state of the patient. Common condition of the client / patientis getting worse because it does not consider the state of nutrition. Various surveys in thehospital and the incident proved foreign hospital malnutrition due to improper nutritionservices and a risk factor.Objective: To determine the nutritional status and dietary food administration in hospitalizedpatients in the department of Prof. Dr. BLU. RD Kandou ManadoMethods: The study was a descriptive cross-sectional observational approach. Thepopulation is all class III patients hospitalized and received food diet. Sample was treatedpatients care class III as much as 95 class, defined by consecutive sampling. Processingand data analysis begins with the editing, coding and then analyzed using SPSS.The results: The level of patient satisfaction on the implementation of the RS diet foodsaverage is 84.9%, the officer friendly attitude 1.4%, 65.2% manners, personal hygiene33.4%. The average intake of nutrients; energy 1775.0kal ± 336.7, 23.9 ± 62.0gr protein, fatand carbohydrates 50.1gr ± 10.6 ± 41.1.Rata 284.2gr average rank of the adequacy ofenergy; 84.6% ± 14.1, 78.2% ± 13.8 protein, fat 12.5 ± 81.3%, carbohydrate 87.5% ± 10.5.Sufficient levels of nutrients in common: energy 13.5 ± 80.4%, protein 78.6% ± 13.8, fat81.3% ± 12.5, carbohydrate 87.5% ± 10.5, average adequacy rate is good (> 80%), ie 75.8%of energy, protein 36.8%, 84.2% fat and 69.2% carbohydrate. The majority of patients(65.3%) and underweight (23.2).